Modulation of hyperpolarization-activated cation current Ih by volatile anesthetic sevoflurane in the mouse striatum during postnatal development. (July 2018) - Sugasawa, Yusuke; Fukuda, Masataka; Ando, Nozomi; Inoue, Ritsuko; Nakauchi, Sakura; Miura, Masami; Nishimura, Kinya
Highlights: Neonate striatal cholinergic neurons already possessed I h . Sevoflurane decreased I h of striatal cholinergic neurons in a dose-dependent manner. Sevoflurane apparently slowed I h activation in the cholinergic neurons. Sevoflurane decreased spike firing during the rebound activation. Abstract: Volatile anesthetics have been reported to inhibit hyperpolarization-activated cyclic-nucleotide gated channels underlying the hyperpolarization-activated cation current ( I h ) that contributes to generation of synchronized oscillatory neural rhythms. Meanwhile, the developmental change of I h has been speculated to play a pivotal role during maturation. In this study, we examined the effect of the volatile anesthetic sevoflurane, which is widely used in pediatric surgery, on I h and on functional I h activation kinetics of cholinergic interneurons in developing striatum. Our analyses showed that the changes in I h of cholinergic interneurons occurred in conjunction with maturation. Sevoflurane application (1–4%) caused significant inhibition of I h in a dose-dependent manner, and apparently slowed I h activation. In current-clamp recordings, sevoflurane significantly decreased spike firing during the rebound activation, which is essential for responses to the sensory inputs from the cortex and thalamus. The sevoflurane-induced inhibition of I h in striatal cholinergic interneurons may lead to alterations of the acetylcholine-dopamine balance in the neural circuits during the early postnatal period.